Prevalence of Anderson-Fabry disease in a cohort with unexplained late gadolinium enhancement on cardiac MRI. (1st April 2020) - Moonen, Avalon; Lal, Sean; Ingles, Jodie; Yeates, Laura; Semsarian, Chris; Puranik, Raj
Abstract: Introduction: Fabry disease is a rare X-linked genetic disorder in which cardiac manifestations include LVH, contractile dysfunction, and fibrosis, visible on cardiac MRI (cMRI) as late gadolinium enhancement (LGE) of the myocardium. Fabry's disease is an important diagnosis to make as treatment is available as lifelong replacement of the deficient enzyme. Aim: To define the prevalence of Fabry disease in a cohort of patients with unexplained LGE on cMRI. Methods: The study population was recruited from patients aged >16 years who had cMRI performed between 2010 and 2018 to investigate LVH, idiopathic LV dysfunction and/or idiopathic ventricular arrhythmia. Patients with 'unexplained' LGE i.e. without a genetic diagnosis of an alternate cardiomyopathy such as HCM or biopsy-proven infiltrative cardiomyopathy such as sarcoid or amyloid, were tested for Fabry disease by either genetic testing or the Dried Blood Spot test ( Sanofi-Genzyme ). Results: Of the 79 patients with unexplained LGE on cMRI, 2 patients tested positive for Fabry disease, both using genetic sequencing techniques. The prevalence of Fabry disease in this selected cohort was 2.5%. Specifically, 1 patient was a 65 year old male and the other patient a 75 year old female. In both cases, the pattern and distribution of LGE on cMRI was of patchy mid-wall enhancement in the inferoseptum. Conclusion: Unexplained LGE on cMRI may be an isolated manifestation of late-onset Fabry disease. This finding should prompt testing for Fabry disease given this is a potentially treatable condition.